A causal investigation on the determinants of CO2 in China. Issue 8 (17th November 2019) - Mele, M.; Randazzo, L.
ABSTRACT: This article examines the causal relationship among carbon dioxide emissions, energy consumption, per capita economic growth, and international trade using temporal econometric models with serial data for the period 1980–2017 in China. In the Armax model all regressors are significant in having influenced the dependent CO2 variable. Subsequently, unidirectional causalities are identified from energy consumption and from commercial opening to carbon dioxide emissions, from commercial opening to energy consumption, from carbon dioxide emissions to per capita economic growth and from economic growth to commercial opening. These results show that, over time, more energy consumption in China results in more carbon dioxide emissions so there will be more environment pollution.